The Impact of Simulated Education and Training on Undergraduate Students’ Disaster Evacuation Competencies - Hawsawi S; Al Thobaity A; Saleh MSM (Advances in Medical Education and Practice)
Sumayyah Hawsawi,1 Abdulellah Al Thobaity,2 Manal Saleh Moustafa Saleh3,4 1Nursing Department, Al Noor Hospital, Makkah, Makkah Region, Saudi Arabia; 2Department of Medical-Surgical Nursing, College of Nursing; Taif University, Taif, Saudi Arabia; 3Nursing Department, College of Applied Medical Science, Shaqra University, Shaqra, Saudi Arabia; 4Nursing Administration, Faculty of Nursing, Zagazig University, Zagazig, Alsharqia, EgyptCorrespondence: Abdulellah Al Thobaity; Manal Saleh Moustafa Saleh, Email Abdulellah.althobaity@hotmail.com; manalmoustafa954@gmail.comBackground: The occurrence of disasters in the world is natural, but we must learn how to deal with their occurrence and mitigate their impact on people and property. It is important to understand how to behave during hospital disasters and properly evacuate the affected areas. Simulation-based education and training are effective ways to increase knowledge, skills, awareness, and experience in the event of an internal hospital disaster.Aim: To evaluate the effectiveness of simulated education and training in enhancing undergraduate nursing students’ disaster evacuation knowledge, skills, and preparedness.Methods: The study utilized a quasi-experimental, single-group pre-and post-test design to assess the impact of simulation training on emergency and disaster preparedness among nursing students. It was conducted in the Simulation Nursing Laboratories at the College of Applied Medical Sciences, Taif University. The sample consisted of 119 undergraduate nursing students, including 60 male students and 59 female students. The Evacuation Disaster Simulation Questionnaire (EDSQ) was used to assess the knowledge and skills of the nursing students. The items cover three key subcategories: time, process, and transportation.Results: The results showed that the mean score of the time in the pre-test group was 1.24± 1.49, while it increased to 3.74± 1.92 in the post-test. In the Process, the mean before the test is 2.23± 1.05 and increased to 3.13± 1.17 after the test. Lastly, in transportation, the mean score of the pre-test group was 3.26± 1.41, but in the post-test group, the mean score on the scale rose to 4.13± 1.28. This indicated an increase in students’ understanding and awareness after the lecture and simulation training with a highly significant improvement (P=0.000).The highest mean score regarding evacuation disaster simulation competencies performance and total scores at pre- and post-educational intervention (Time (3.73), Process (3.13), and Transportation (4.12). Moreover, total scores (39.66) for the study group post-intervention program with a highly significant improvement (P= 0.000).Conclusion: We can see the effectiveness and impact of education through simulation on students, indicating an increase in students’ knowledge, understanding, and awareness after the lecture and simulation training.Keywords: hospital disasters, simulation education, evacuation simulation, evacuation disaster, nursing students